Lesion Site Is the Key Prognostic Factor for Keloid Patients Receiving Surgery With Adjuvant Radiotherapy. Issue 6 (28th December 2022) - Chen, Frank; Kuo, Yur-Ren; Huang, Chih-Jen; Tang, Jen-Yang; Chiang, Chen-Han; Huang, Ming-Yii
Abstract : Background: Keloid is a benign tumor with high recurrence rate; accordingly, complete surgical excision with adjuvant radiotherapy is one of the most effective treatments. This study reviewed outcomes of keloid patients receiving surgery and adjuvant radiotherapy in Kaohsiung Medical University Hospital. Materials and Methods: All patients received radiation dose with 15 Gy, with their first radiotherapy within 24 hours after surgical excision. The end points were recurrence rate and local recurrence-free interval (LRFI), defined clinically as palpable gross tumor over the treatment site and duration from the last day of radiotherapy to disease recurrence. Results: From May 2017 to July 2020, 32 patients with 40 keloid lesions were included. The mean age for these patients was 37.6 years, and the median follow-up time was 15.3 months. The overall recurrence rate was 52.5%, and the median LRFI was 9.7 months. Recurrence rates for males and females were 46.7% and 56% ( P = 0.567), respectively; for head and ear, chest, shoulder and upper extremities, and abdomen and back were 12.5%, 61.5%, 63.6%, and 62.5% ( P = 0.093); for lesions over 20 cm 2 and below 20 cm 2 were 62.5% and 50% ( P = 0.527); and for megavoltage electron beam and kilovoltage photon beam were 56.7% and 40% ( P = 0.361), respectively. Patients were further classified into 2 groups by lesion sites, which showed lower recurrence rate ( P = 0.011) and longer LRFI ( P = 0.028) with lesions over the head and ear than other sites. Conclusions: We found that lesion site might be a prognostic factor for keloid recurrence. Adjuvant radiation dose escalation for high-recurrence risk areas (other than the head and ear) might be required.